ANTIBACTERIAL EFFECTIVENESS OF PROSOPIS JULIFLORA AGAINST AEROBIC AND ANAEROBIC BACTERIA - V., AISHWARYA; G., BHUVANESHWARI; GRACE, J. R. LILLY; VENNILA, ROSY (International Journal of Current Pharmaceutical Research, 2020)
Objective: The aim of this study is to analyse the antibacterial effectiveness of the leaf extract of Prosopis juliflora against aerobic and anaerobic bacteria and the objectives include maintaining the culture of Clostridium perfringens ATCC 3624, Staphylococcus aureus ATCC 25923, E. coli ATCC 25922 and to obtain an extract from the leaves of Prosopis juliflora by water extraction method. Agar cup diffusion testing is carried out to test the effectiveness of the extracted herb against the isolated strains of the above-mentioned bacteria. Methods: Cross-sectional study was conducted for 6 mo in the Clinical Microbiology Laboratory at SMCH. Extract from the leaves of Prosopis juliflora was collected by a water extraction method. Isolation of Clostridium perfringens (from RCMB), Staphylococcus aureus and Escherichia coli were done, following which the agar cup diffusion method was performed in which the collected extracts were placed as discs in the agar plate which had been inoculated with the strains of the isolated bacteria. The agar plate was then incubated anaerobically. Agar cup diffusion method is considered as a primary method to determine the antimicrobial effectiveness of the bacteria. Results: The leaf extract of Prosopis juliflora was found to be effective against both aerobic and anaerobic bacterial strains. Conclusion: Based on the work, the effectiveness of Prosopis juliflora was determined and the mechanism of susceptibility was identified. With future research works in the field, many such natural herbal extracts can be proven to be effective against many pathogenic microorganisms.